2007
DOI: 10.1002/chin.200729235
|View full text |Cite
|
Sign up to set email alerts
|

Boron — A Key Element in Radical Reactions

Abstract: Boron derivatives are becoming key reagents in radical chemistry. Here, we describe reactions where an organoboron derivative is used as a radical initiator, a chain-transfer reagent, and a radical precursor. For instance, B-alkylcatecholboranes, easily prepared by hydroboration of alkenes, represent a very efficient source of primary, secondary, and tertiary alkyl radicals. Their very high sensitivity toward oxygen-and heteroatom-centered radicals makes them particularly attractive for the development of radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Borane derivatives are now becoming key reagents in radical chemistry, and have been used to develop an attractive new procedure for the reduction of radicals with alcohol and water [17]. To clarify the mechanism of grafting of trialkylborane-initiated MMA resins with protein materials, we review here the results of our previous studies [18][19][20] on the basis of published materials and current knowledge.…”
Section: Hohmentioning
confidence: 99%
See 2 more Smart Citations
“…Borane derivatives are now becoming key reagents in radical chemistry, and have been used to develop an attractive new procedure for the reduction of radicals with alcohol and water [17]. To clarify the mechanism of grafting of trialkylborane-initiated MMA resins with protein materials, we review here the results of our previous studies [18][19][20] on the basis of published materials and current knowledge.…”
Section: Hohmentioning
confidence: 99%
“…More recently, Penaud et al [17] have reported that homolytic substitution at borane moieties does not proceed with carbon-centered radicals, and that many different types of heteroatom-centered radicals (e.g., alkoxyl radicals) react efficiently with organoboranes. The first step of homolytic substitution is the formation of a Lewis acid-base complex between the borane and the radical.…”
Section: Tri-n-butylborane As a Polymerization Initiatormentioning
confidence: 99%
See 1 more Smart Citation
“…4 Boron derivatives have been characterized as key reagents in radical chemistry, and triethylborane is used as an effective low temperature initiator in radical reactions. 5 Boron has long been regarded as a good candidate for rocket fuel additives, due to its high energy density, and its incorporation results in complex high temperature chemistry involving boron radicals. 6 In these contexts, information on new boron radicals is both interesting and scientifically valuable.…”
Section: Introductionmentioning
confidence: 99%
“…The SF 5 Cl addition on unsaturated compounds goes through a free-radical mechanism, and is promoted by the radical activation of SF 5 Cl by Et 3 B, which leads to the formation of the propagating species SF 5 • [ 32 33 ]. Trialkylboranes are common low-temperature radical initiators, and Et 3 B is one of the most used in the literature [ 34 35 ]. The use of the reagent allows the radicals to form, even at very low temperature, due to its strong reactivity with oxygen.…”
Section: Introductionmentioning
confidence: 99%